2018
DOI: 10.1021/acs.langmuir.8b02034
|View full text |Cite
|
Sign up to set email alerts
|

On the Oblique Impact Dynamics of Drops on Superhydrophobic Surfaces. Part I: Sliding Length and Maximum Spreading Diameter

Abstract: Oblique water drop impacts were performed on a superhydrophobic surface at normal Weber numbers in the range of 3 < We < 80 and at angles of incidence in the range of 0 < AOI < 60°. While holding We constant, we varied the AOI to investigate how the oblique nature of the impact affects the sliding length and spreading diameter of impacting drops. Our sliding length measurements indicate that drops impacting at We < 10 retain essentially full mobility on the surface, whereas the sliding of higher- We impacts is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 36 publications
2
32
0
Order By: Relevance
“…However, the relationship between D max and We tends to slightly vary among different studies depending on the surface tested. 30,38,39 Here, we measured the maximum spreading diameter of drops impacting on the horizontal superhydrophobic surface and obtained the scaling of D max ≈ 0.79 D 0 We n 0.29 through the regression fitting, as shown in Figure 5a. Yeong et al have built a theoretical model for the maximum spreading in the tangential direction as D y max * = D max * + cWe t , where c ( c > 0) is the scaling factor and We t is the Weber number component in the tangential direction, expressed as We t = tan 2 α We n .…”
Section: Resultsmentioning
confidence: 99%
“…However, the relationship between D max and We tends to slightly vary among different studies depending on the surface tested. 30,38,39 Here, we measured the maximum spreading diameter of drops impacting on the horizontal superhydrophobic surface and obtained the scaling of D max ≈ 0.79 D 0 We n 0.29 through the regression fitting, as shown in Figure 5a. Yeong et al have built a theoretical model for the maximum spreading in the tangential direction as D y max * = D max * + cWe t , where c ( c > 0) is the scaling factor and We t is the Weber number component in the tangential direction, expressed as We t = tan 2 α We n .…”
Section: Resultsmentioning
confidence: 99%
“…Recently researches have shown that inclined surfaces or moving horizontal surfaces are beneficial to reduce contact time [ 25–28 ] and inhibit splash, [ 39 ] and droplets show an asymmetric dynamic at the retraction stage. [ 30,31 ] Li et al. reported the rapid rebound of the droplet on inclined microflower superhydrophobic surface and ascribed it to the sudden contraction of the trailing edge.…”
Section: Introductionmentioning
confidence: 99%
“…Recently researches have shown that inclined surfaces or moving horizontal surfaces are beneficial to reduce contact time [25][26][27][28] and inhibit splash, [39] and droplets show an asymmetric dynamic at the retraction stage. [30,31] Li et al reported the rapid rebound of the droplet on inclined microflower superhydrophobic surface and ascribed it to the sudden contraction of the trailing edge. [32] LeClear et al fabricated two kinds of superhydrophobic groove surfaces with different orientations and observed droplet asymmetric retraction on 60° inclined surface.…”
mentioning
confidence: 99%
“…In nature and industrial fields, the droplet encounters various solid surface, such as curve, textured, and inclined surface [24][25][26][27][28][29][30][31][32][33][34]. Compared with the flat horizontal surface, the outcomes are more complex, and the results may be different.…”
Section: Introductionmentioning
confidence: 99%
“…It is demonstrated that the droplet impacting an inclined surface behaves asymmetry between the tangential and lateral direction along the surface, which can promote the droplet to rebound from the surface. Meanwhile, due to the tangential velocity, the droplet slides along the inclined surface, away from the impact position [31][32][33]. If two droplets impact an inclined surface successively, the off-center impact should be observed, which is different from horizontal surface and still poorly understood, especially on superhydrophobic surfaces.…”
Section: Introductionmentioning
confidence: 99%